SYNTHESIS OF UK-3A ANALOGUE AND ASSAY ON P 388 MURINE LEUKEMIA CELLS - Y Anita; M Hanafi; AMJ Putra; S Arifin; Y Usuki; H Iio (Indonesian Journal of Chemistry, 2007)
UK-3A is secondary metabolite of Streptomyces sp.517-02 which has IC50 38 µg/mL against P388 Murine Leukemia cells. An analogue of UK-3A was synthesized from L-methyl serine as the starting material by amidation and esterification. An analogue UK-3A was analyzed and identified by TLC, FT-IR, LC-MS and NMR spectrometer. It was found to have IC50 15.4µg/mL against the same Leukemia cells. The overall yield was 87.10%.